RELATIVE EFFICACY OF BIOPESTICIDES AND NEWER INSECTICIDES AGAINST HELICOVERPA ARMIGERA (HUB.) IN TOMATO - S. K. JAT,; O. P. AMETA, (The Bioscan, 2013)
Relative efficacy of biopesticides and newer insecticides against Helicoverpa armigera (Hub.) on tomato was evaluated in field conditions. The results showed that the three applications of flubendiamide 480 SC at 200 mL/ ha was found significantly most effective, which caused highest mean reduction of population of tomato fruit borer larvae and fruit damage, 89.94 and 3.10 per cent. It was followed by spinosad 45 SC at 200 mL/ha and HaNPV at 250 LE/ha with 74.67 and 74.10 per cent mean reduction, respectively and were at par with each other and the spinosad 45 SC @ 200 mL/ha observed (4.86) per cent fruit damage followed by HaNPV 250 LE/ha, Bt @1.5 kg/ha and Beta-cyfluthrin 2.5 SC were found moderately effective treatment being 8.16, 10.14 and 6.68 per cent fruit damage, respectively. The highest marketable yield of 265.68q/ha was recorded in case of Flubendiamide 480 SC @ 200 mL/ha with highest C: B ratio of 1:2.075. It was followed by Spinosad 45 SC @ 200mL/ha (251.29 q/ha) and Beta-cyfluthrin 2.5 SC @ 750 ml/ha (238.38 q/ha).